Enhancing English Language Proficiency for Sustainable Tourism in Sabang: A Focus Group Discussion for the "Kampung Inggris Sabang" Program - Cut Dian Fitri; Khairul Azmy; Danil Akbar Taqwadin; Amrullah Amrullah; Cut Zahri; Fahmi Yunus; Natasya Zillah (Jurnal Nispatti, 2026)
Sabang's rise as a Free Trade Zone, Free Port, and National Tourism Strategic Area has increased international visitor flows, exposing a critical gap: many local tourism stakeholders (homestay operators, tour guides, MSMEs, transport providers) lack the English proficiency needed to deliver high-quality, culturally authentic services. This community-service study proposes and grounds the Kampung Inggris Sabang initiative using Focus Group Discussions (FGDs) to map needs, identify barriers, and co-design an actionable language-empowerment roadmap. Employing a qualitative design, the study engaged diverse stakeholders in structured FGDs and semi-structured interviews to examine current communicative competence, motivation, contextual language requirements, and institutional readiness. Thematic analysis reveals (1) a strong community motivation to acquire practical, tourism-specific English; (2) constraints including limited access to localized training, time/ work pressures, and lack of context-driven materials; and (3) preference for flexible, task-based, and digitally supported learning models embedded in local practice. Based on these findings, the paper outlines curriculum principles English for Specific Purposes (Tourism), task-based learning, role-plays, and peer mentoring and proposes institutional partnerships for sustainability. The study concludes that a participatory, context-sensitive Kampung Inggris Sabang can improve service quality, foster inclusive economic benefits, and strengthen Sabang's competitiveness as a sustainable international destination.